Background of complex treatment in dependence on intensity of destructive processes in parodontal tissues - Dimitrova, A. (Actual Dentistry, 2018)
Goal: develop index programs for assessing the state of periodontal tissues. Material and methods. Clinical and laboratory examination of 126 patients aged 19–25 years. It was found out that in these patients the pathological process with the same diagnosis generalized periodontitis of the initial–I degree with different degrees of intensity. The nature and intensity of the dystrophic-inflammatory process depends on the aggressiveness of local irritant factors and, first of all, on the presence of approximated carious lesions, and the health of the oral cavity, in particular, of interdental hygiene. Formation of periodontal pockets and their number are in direct correlation with approximative carious lesions. In the diagnosis of generalized periodontitis in young people, the number and degree of severity of destructive lesions of periodontal disease and hard tissues of the tooth, that is, the intensity of the pathological process in the periodontal disease, were taken into account. Results. Persons of a young age of 19–25 years old with the same diagnosis generalized periodontitis of the initial–I degree had a different degree of destructive lesions both in the alveolar bone and in the hard tissues of the tooth. Taking into account the results of the analysis, the indixes for assessing the intensity of inflammatory and destructive processes in periodontal tissues were developed: the index of periodontal destruction (IDP) and the total index of periodontal disease (TIDP), which allows planning of the individual volume of treatment and preventive measures. Conclusion. Correct and timely diagnosis of generalized periodontitis by definition of the degree of intensity of the pathological process, contributes to the development of individual schemes of hygienic and therapeutic and prophylactic measures. Such a differentiated approach contributes to maintaining the function and integrity of periodontal tissues in patients Key words: generalized periodontitis, intensity of defeat of periodontal tissues, indixes.